THE CORRELATION BETWEEN THE FREQUENCY OF WATCHING BIMODAL SUBTITLED VIDEOS AND STUDENTS’ LISTENING COMPREHENSION - Millenia Berlian Febrina (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
Listening was a skill that language learners must have. In several studies, listening was an activity that was avoided by English learners due to various factors, but now students were used to practicing listening by watching English videos. This study was a correlational study that aimed to find out how was the correlation between the frequency of watching bimodal subtitled video and students’ listening comprehension as well as providing their perceptions toward the use of bimodal subtitled videos for listening practice. This study involved 36 students of 10th grade in Krian, East Java who had participated in a listening program to watch bimodal subtitled videos for two weeks at school. The collected data were analyzed statistically using SPSS 16. The results of the study reported that there was a significant positive correlation between students’ frequency of watching bimodal subtitled videos and their listening comprehension (r = 0.459, p = 0.05). Students also showed positive perceptions of the use of bimodal subtitled videos for listening practice. It could be concluded that students' frequency of watching bimodal subtitled videos was positively related to their listening comprehension and received good responses from them. Therefore, teachers could use bimodal subtitled videos for listening learning activity at school.